The influence of fibre orientation in self-compacting concrete on 4-point bending strength - Heiko Herrmann; Oksana Goidyk; Hendrik Naar; Tanel Tuisk; Andres Braunbrück (Proceedings of the Estonian Academy of Sciences, 2019)
This contribution presents the performed experiments and experimental setup in detail for future reference and the results of bending tests performed on steel fibre concrete beam specimen, which have been cut out of a larger plate. These beams have different fibre orientation distributions, due to being taken from different parts of the plate and with different orientation with respect to the flow of the fresh concrete.